Enhancement in optoelectronic properties of europium-doped ZnS thin films prepared by nebulizer spray technique for UV photodetection applications. (15th June 2022) - Dharani Devi, M.; Vimala Juliet, A.; Ade, Ramesh; Thirumoorthi, M.; Diana, P.; Saravanakumar, S.; Ganesh, V.; Bitla, Yugandhar; Algarni, H.
Abstract: In this work, structural, optical, photoluminescence, and photoconductivity properties of Eu 3+ (0, 1, 3, and 5%) doped ZnS thin films are investigated. These thin films are fabricated by a low-cost spray pyrolysis method. The structural studies confirm the single-phase nature of pure and Eu 3+ doped ZnS thin films and these films crystallize into hexagonal wurtzite structure. Optical properties disclose the semiconductor behavior of the films. The optical bandgap ( E g ) values of the films are found to be 3.66, 3.62, 3.50, and 3.55 eV for ZnS, ZnS:Eu (1%) ZnS:Eu (3%) and ZnS:Eu (5%), respectively. Photoluminescence spectra of the films exhibit a high intensity visible and broad UV emission band centered at the wavelengths of 487 and 400 nm, respectively. ZnS:Eu (3%) photo-detector exhibits high responsivity, external quantum efficiency (EQE), and detectivity of 1.12 × 10 −2 AW −1, 3.59% and 4.86 × 10 9 Jones, respectively among all the fabricated films. The present study reveals that Eu 3+ doped ZnS thin film especially around 3% concentration of Eu 3+ can be a potential candidate for technological applications in the semiconductor optoelectronic field.